PEMBELAJARAN KITAB TAFSIR AL-MUNIR DAN INTEGRASI NILAI-NILAI AKHLAK DALAM PERILAKU KIAI ZAINAL ALIM (Studi Kasus Di MA Zainul Ulum, Ganjaran Gondanglegi) - Agus Miftah Faiz; Luqman Hakim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Developing student character through education based on the teachings of the Qur'an requires a balanced blend of textual study and concrete examples from teachers. This study focuses on documenting how the moral teachings in the Tafsir Al-Munir compiled by Sheikh Nawawi al-Bantani (especially QS. Luqman verses 18-19) are manifested through the actions of Kiai Zainal Alim, while also measuring its influence on the character development of students at MA Zainul Ulum Ganjaran, Gondanglegi, Malang. A qualitative method with a case study design was chosen to conduct this research by collecting information through in-depth interviews, direct observation, and document searches processed using interactive analysis techniques ala Miles and Huberman (data filtering, information presentation, and drawing conclusions). Findings in the field indicate that the instillation of moral principles is implemented through teaching the bandongan and ijmali systems; in the process, teachings about rejecting arrogance, the need for humility, and polite walking and speaking manners are directly reinforced by Kiai Zainal Alim's daily example. These concrete examples (uswah hasanah) have proven effective in instilling good values ​​into the students' souls, as evidenced by their increasingly polite speech, heightened mutual respect, and growing humility in daily school life. Ultimately, this study confirms that a teacher's concrete example is a key determinant of the success of tafsir teaching in fostering student character.